LEARNING EVALUATION WITH ARTIFICIAL INTELLIGENCE TECHNOLOGY INTEGRATION TOWARDS IMPROVING STUDENT LEARNING QUALITY - Hendra Wijaya; Hendro Prasetyono (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This research emerged from the issue of the limited effectiveness of traditional  learning approaches in improving students’ academic performance. The primary  goal of this study is to quantitatively examine how far the integration of Artificial  Intelligence (AI)–based learning methods can enhance students’ learning outcomes  compared to conventional lecture techniques. A quantitative experimental design  utilizing a pretest–posttest model was applied. Data were obtained through pretests  and posttests and further analyzed using the Paired Sample t-test and Analysis of  Covariance (ANCOVA) to determine differences and measure the influence of  learning methods on achievement levels. The results indicate a substantial improvement between the pretest and posttest  scores, with a mean difference of -15.167 (t = -9.575; p < 0.001), confirming that  posttest scores significantly increased after the intervention. The ANCOVA results  further demonstrated that the applied learning method had a strong influence on  posttest outcomes (F = 35.980; p < 0.001), while the pretest variable showed no  significant effect (p = 0.497). Participants who engaged in AI-integrated learning  achieved an average posttest score of 85.838, notably higher than the lecture  group’s 75.729, with a 95% confidence interval verifying this difference. These  findings emphasize that AI integration enhances learning personalization,  comprehension, and engagement, thereby contributing positively to the overall  improvement of learning outcomes compared to traditional methods. The  implications of this research underscore the importance of educational institutions  integrating AI-based learning to enhance the quality of the learning process,  support more accurate pedagogical decision-making, strengthen curriculum policy  development, and promote the systematic, sustainable, inclusive, and adaptive  implementation of teacher training.